Enrichment Of Yarn Quality By The Change Of Drafting Zone Of Drawing Machines (Daffodil International University Journal of Science and Technology, 2011)
In Drawing frame, different pin settings were used to produce 5lbs/spy jute yarn in apron draft spinning frame. Among the pin settings of 1st draw frame: Draft-4.0, 2nd draw frame: 6.3 and 3rd draw frame: 5.4, Doubling- 2:1, 3:1 and 2:1 respectively achieved the highest quality at modified pin settings for said jute yarn. In this experiment, existing pins of 3rd Drawing frame were replaced by new sets of pins with different density, size and shape and yarns were produced from both systems. Physical properties of produced yarn were tested and found modified pins density shows better quality yarn. DOI: http://dx.doi.org/10.3329/diujst.v6i1.9329 DIUJST 2011; 6(1): 17-19